Production of Coenzyme Q10 and Carotenoid by Cultivation of Rhodopseudomonas sp. OS33-UV13-5 Using Raw Starch as Carbon Source - Krairak, Somchai (Journal of Science Ladkrabang, 2023)
Rhodopseudomonas sp. OS33-UV13-5 is the photosynthetic bacterial mutant strain obtained from a genetic improvement of Rhodopseudomonas sp. OS33 by UV irradiation. Rhodopseudomonas sp. OS33-UV13-5 showed the ability to digest raw starch, resulting in a problem-solving of the medium viscosity and a decrease in an energy consumption due to the direct degradation of raw starch particles. The result showed that Rhodopseudomonas sp. OS33-UV13-5 gave the highest growth at 11.82±0.935 U770nm, carotenoid concentration of 15.67±1.137 mg/L, and coenzyme Q10 concentration of 288.79±20.132 µg/L in cells cultivated in medium containing 300 g/L of raw starch under light intensity of 1,500 lux. They were 5.65, 2.00, and 1.44 times, respectively, higher than those from cells cultivated in medium containing 10 g/L of raw starch under light intensity of 1,000 lux. Under optimal conditions, a promising hydrolysis of raw starch to glucose as well as glucose utilization provided the lower glucose concentration than 2.0 g/L during a cultivation which promoted not only bacterial growth but also a production of carotenoid and coenzyme Q10. Finally, the relationship between the growth and raw starch amylase activity was demonstrated. During the cultivation of Rhodopseudomonas sp. OS33-UV13-5, the glucose level was found at 0.12±0.08 to 1.18±0.15 g/L.